Strategic competence of junior high school students in solving geometry problems reviewed from sex differences - Firdiana, Winda; Juniati, Dwi; Janet Trineke Manoy (Universitas PGRI Kalimantan, 2022)
This study aims to describe the strategic competence of junior high school students in solving geometry problems in terms of gender differences. The indicators assessed include formulating, representing and solving problems. The subjects of this study were 1 male student and 1 female student in class IX-F of SMPN 1 Tulangan who had equal abilities. Furthermore, the subject worked on the task of solving geometry problems. The results showed that both subjects understood the problem by reading and drawing. In the first problem, the two subjects represented the problem by shading, calculating the area of ​​the warehouse and land using a rectangular area and then solving the problem by calculating the area of ​​the cut grass multiplied by the cost of cutting services. However, the female subject did not describe the shape of the object accurately and did not give a precise reason for the shape that had been described. In the second question, the two subjects chose the wrong strategy in representing the problem because they were unable to make another cardboard arrangement, as a result the process of solving the problem was wrong. Students need to be trained on non-routine geometry questions to develop their strategic competencies.